Representasi Maskulinitas dalam Iklan - Kurnia, Novi (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
The phenomenon of hegemonic masculinity have been well understood, despite the fact that mass media in general and advertisement in particular, is a medium for contestation between masculinity and feminity. This article shows that, new feature of masculinity has come due to the adaptation of feminity. The new feature of masculinity has been known as metrosexual.